Current practices and expectations to reduce Electrophysiology catheters environmental impact: a large EHRA/LIRYC European survey. (19th May 2022) - Boussuge-Roze, J; Boveda, S; Anic, A; Conte, J; Chun, JKR; Marijon, E; Legentil, X; Mekongo, V; Sacher, F; Jais, P
Abstract: Funding Acknowledgements: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Boston Scientific Background: Despite aiming at improving patients' health, healthcare consumes a large amount of resources and contributes to 4.6% of the global GHG/carbon emissions, 71% of the footprint being due the supply chain. It also produces millions of tons of complex waste per year. Yet, sustainability in EP remains a complex challenge as the performance and safety for patients are critical. Objective: To set the ground to reduce electrophysiology (EP) catheters' environmental impact. Methods: A survey was conducted to poll European EP centers on 24 questions on sustainability practices and expectations. Results: 278, mostly EP doctors (84%, 76% male, 43yo), working in a public environment (89%, >100 procedures/year in 53% and > 500 in 36%) participated. A majority of EP doctors uses 2 to 4 more catheters/sheath per paroxysmal AF ablation procedure. MAPPING/ABLATION catheters are discarded after the procedure (73&78%), with partial re-cycling (electrodes) in 23&26 %. Local/external sterilization is rarely used (12% & 9%). Catheters' packaging are discarded in medical or general waste (38 & 31%) while it is recycled in only 19%. EP Healthcare professionals are highly motivated in being environment friendly in their personal (82%) and in EP practice (62%). They identify a lack of interest from their hospital in 59% (only 16% having an executive in charge). Other barriers are the complexity of sustainability processes (48%), the effort required to change practice (47%), infectious risk (41%), lack of training (37%) and cost (33%). EP Healthcare professionals would favor sustainable mapping /ablation catheters if performances were preserved (60 & 50%). They consider re-use as the most relevant solution (60%) while being currently illegal in some European countries. Packaging should be reduced in size or made reusable. Finally, they consider that regulatory (31%), education (19%) and recommendations by companies (19%) would encourage the field to transition to more environmentally friendly practices. Interestingly, age, gender, type of practice, country or experience did not impact the results. Conclusion: EP Healthcare professionals demonstrate a willingness to adopt sustainable practices. They consider re-use as the most relevant approach as of today. 60/50 % would favour sustainable mapping/ablation catheters providing preserved performances. Leaping to the next level of sustainability will request development of new sustainable solutions, models and technologies. Reaching this urgent goal will require governments, industry, hospitals and doctors to work closely in a coordinated approach.